Modified zinc negative electrode, preparation method thereof and aqueous zinc ion battery

By forming an alkaline zinc sulfate layer in situ on the surface of the zinc negative electrode of the aqueous zinc ion battery, the problems of side reactions such as zinc negative electrode dendrites growth, corrosion and hydrogen evolution are solved, and the coulomb efficiency and cycle stability of the battery are significantly improved.

CN119905571APending Publication Date: 2025-04-29THE HONG KONG POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311408588.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The zinc negative electrode in the aqueous zinc ion battery has side reactions such as dendrite growth, corrosion and hydrogen evolution, resulting in low Coulomb efficiency and poor circulation stability.

Method used

By forming an alkaline zinc sulfate layer in situ on the surface of the zinc negative electrode substrate, a uniform protective layer is formed to regulate zinc ion deposition and prevent the occurrence of side reactions.

Benefits of technology

It effectively avoids the growth of zinc dendrites, reduces side reactions such as corrosion and hydrogen evolution, and improves the coulombic efficiency and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905571A_ABST
    Figure CN119905571A_ABST
Patent Text Reader

Abstract

The invention relates to an electrochemical energy material, and provides a modified zinc negative electrode and a preparation method thereof.The modified zinc negative electrode comprises a zinc negative electrode base material and a basic zinc sulfate layer coating at least part of the surface of the zinc negative electrode base material, and the basic zinc sulfate layer is uniformly generated on the surface of the zinc negative electrode base material in situ. The preparation method of the modified zinc negative electrode comprises the following steps: soaking the zinc negative electrode base material in a sulfate aqueous solution, and growing the basic zinc sulfate layer on the surface of the zinc negative electrode base material in situ to obtain the modified zinc negative electrode. The basic zinc sulfate layer is deposited on the surface of the modified zinc negative electrode through the in-situ reaction, side reactions of the zinc negative electrode are effectively inhibited, the modified zinc negative electrode serves as a negative electrode material of an aqueous zinc ion battery, coulombic efficiency and cycling stability of the battery can be improved, and the modified zinc negative electrode is simple in preparation method, mild in reaction condition and suitable for industrial production. The method is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electrochemical energy materials, and in particular relates to a modified zinc negative electrode and a preparation method thereof, and an aqueous zinc ion battery. Background Art

[0002] Aqueous zinc-ion batteries, also known as water-based zinc batteries, are high-safety batteries that use water-based electrolytes to replace the flammable organic electrolytes used in traditional lithium-ion batteries.

[0003] At present, aqueous zinc-ion batteries have attracted much attention because of the advantages of the zinc negative electrode they use, such as high specific capacity, low redox potential, low cost, abundant resources, safety and stability, and easy processing. In addition, the aqueous electrolyte used has the characteristics of intrinsic safety, high ionic conductivity, and environmental friendliness. Therefore, rechargeable aqueous zinc-ion batteries have become one of the most promising electrochemical energy storage devices in recent years.

[0004] However, during the charge and discharge process of aqueous zinc-ion batteries, side reactions such as zinc dendrite growth, corrosion and hydrogen evolution at the zinc negative electrode seriously damage the coulombic efficiency and cycle stability of the battery. Summary of the invention

[0005] The purpose of the present application is to provide a modified zinc negative electrode and a preparation method thereof, as well as an aqueous zinc ion battery, aiming to solve the problem of low coulombic efficiency and poor cycle stability of the battery caused by side reactions such as dendrite growth in the zinc negative electrode of the existing aqueous zinc ion battery.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a modified zinc negative electrode, comprising a zinc negative electrode substrate and a basic zinc sulfate layer coated on at least a portion of the surface of the zinc negative electrode substrate, wherein the basic zinc sulfate layer is generated in situ on the surface of the zinc negative electrode substrate.

[0008] In one embodiment of the first aspect, the thickness of the basic zinc sulfate layer is 3 μm to 60 μm.

[0009] In one embodiment of the first aspect, the zinc negative electrode substrate comprises at least one of zinc foil, zinc foam or electroplated zinc; and / or,

[0010] The thickness of the zinc negative electrode substrate is 0.01 mm to 0.5 mm.

[0011] In a second aspect, the present application provides a method for preparing a modified zinc negative electrode, comprising the following steps:

[0012] The zinc negative electrode substrate is placed in a soaking solution for soaking treatment, wherein the soaking solution includes a first solution, and the first solution is a sulfate aqueous solution. The basic zinc sulfate layer is in situ grown on the surface of the zinc negative electrode substrate to obtain a modified zinc negative electrode.

[0013] In one embodiment of the second aspect, the solute of the sulfate solution includes at least one of zinc sulfate, sodium sulfate, potassium sulfate or ammonium sulfate.

[0014] In one embodiment of the second aspect, the soaking treatment time is 12 hours to 120 hours; and / or,

[0015] The immersion treatment temperature is 25°C to 40°C; and / or,

[0016] The pH value of the soaking solution is 2 to 7; and / or,

[0017] The concentration of the sulfate aqueous solution is 0.1 mol / L to 3 mol / L.

[0018] In one embodiment of the second aspect, the soaking solution further includes a second solution, which is an aqueous solution containing at least one anion selected from the group consisting of chloride ions, fluoride ions, acetate ions, and phosphate ions.

[0019] In one embodiment of the second aspect, the immersion treatment comprises the following steps: first immersing the zinc negative electrode substrate in the first solution, and then transferring the zinc negative electrode substrate to the second solution for immersion.

[0020] In one embodiment of the second aspect, the zinc negative electrode substrate is pretreated and then placed in the soaking solution, and the pretreatment comprises the following steps: placing the zinc negative electrode substrate in an organic solvent for ultrasonic treatment.

[0021] In one embodiment of the second aspect, the organic solvent comprises at least one of ethanol, isopropanol or acetone.

[0022] In a third aspect, the present application provides an aqueous zinc ion battery, comprising a negative electrode, a positive electrode and an electrolyte, wherein the negative electrode is the modified zinc negative electrode as described above.

[0023] In one embodiment of the fourth aspect, the positive electrode includes at least one of manganese dioxide, vanadium pentoxide, sodium vanadate, copper vanadate, zinc vanadate, activated carbon or polyaniline.

[0024] The modified zinc negative electrode provided in the first aspect of the present application has a basic zinc sulfate layer uniformly deposited on the surface of the zinc negative electrode through an in-situ reaction. The basic zinc sulfate layer has a uniform zinc ion mass transfer channel and a relatively high zinc ion conductivity, which can effectively regulate the uniform deposition of zinc ions and avoid the growth of zinc dendrites. At the same time, the low electronic conductivity and physical shielding effect of the basic zinc sulfate protective layer isolate the contact between the electrolyte and the metallic zinc, preventing the occurrence of side reactions such as corrosion and hydrogen evolution. Therefore, using the modified zinc negative electrode provided by the present application as the negative electrode material of an aqueous zinc ion battery can improve the coulombic efficiency and cycle stability of the battery.

[0025] The second aspect of the present application provides a method for preparing a modified zinc negative electrode, which can obtain a modified zinc negative electrode with a basic zinc sulfate protective layer in situ grown on its surface by immersing the zinc negative electrode substrate in a sulfate solution. The preparation method is simple, the reaction conditions are mild, and it is suitable for large-scale production.

[0026] The aqueous zinc ion battery provided in the third aspect of the present application adopts the modified zinc negative electrode provided in the present application, which improves the problem of corrosion and side reactions such as hydrogen evolution of the zinc negative electrode, and achieves significant improvements in coulombic efficiency and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 The cycle comparison diagram of the battery assembled with the modified zinc negative electrode and the original zinc negative electrode in Example 1 of the present application (a is 5mA / cm 2 The current density is 10 mA / cm 2 current density);

[0029] Figure 2 The cycle comparison diagram of the battery assembled with the modified zinc negative electrode and the original zinc negative electrode in Example 2 of the present application (a is 2 mA / cm 2 The current density is 10 mA / cm 2 current density);

[0030] Figure 3 1 is a comparison chart of the coulombic efficiency of the battery assembled with the modified zinc negative electrode and the original zinc negative electrode respectively in Example 2 of the present application;

[0031] Figure 4The cycle comparison diagram (a) and the coulomb efficiency comparison diagram (b) of the battery assembled with the modified zinc negative electrode and the original zinc negative electrode respectively in Example 6 of the present application;

[0032] Figure 5 The cycle comparison diagram (a) and the coulomb efficiency comparison diagram (b) of the battery assembled with the modified zinc negative electrode and the original zinc negative electrode respectively in Example 8 of the present application;

[0033] Figure 6 The figures are the cycle comparison diagram (a) and the coulomb efficiency comparison diagram (b) of the battery assembled with the modified zinc negative electrode and the original zinc negative electrode respectively in Example 9 of the present application;

[0034] Figure 7 It is a cycle comparison diagram (a) and a coulomb efficiency comparison diagram (b) of the battery assembled with the modified zinc negative electrode and the original zinc negative electrode respectively in Example 10 of the present application. DETAILED DESCRIPTION

[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0036] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0037] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0038] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0039] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0040] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0041] In response to the defects of the zinc negative electrode of aqueous zinc ion batteries, researchers have adopted strategies including regulating the electrolyte composition, designing the zinc electrode structure, modifying the diaphragm and constructing a zinc surface protective layer. Among them, constructing a zinc negative electrode surface protective layer is considered to be an effective strategy to improve the cycle stability of aqueous zinc ion batteries because it can effectively regulate the mass transfer and deposition behavior of zinc ions and hinder direct contact between water and the zinc negative electrode. However, the current preparation process of the artificial protective layer of the zinc negative electrode is complicated, which hinders the practical application of these strategies. Therefore, the embodiments of the present application provide the following scheme.

[0042] In a first aspect, an embodiment of the present application provides a modified zinc negative electrode, comprising a zinc negative electrode substrate and a basic zinc sulfate layer coated on at least a portion of the surface of the zinc negative electrode substrate, wherein the basic zinc sulfate layer is generated in situ on the surface of the zinc negative electrode substrate.

[0043] Uneven zinc deposition is prone to occur on the zinc negative electrode, leading to rapid dendrite growth and rapid battery failure. At the same time, severe side reactions on the zinc negative electrode will consume the active zinc source, reduce its utilization rate and cause surface passivation, which increases the internal resistance of the battery. When the current density or surface capacity increases, the growth of dendrites accelerates, and its loose structure and increased exposed surface will also aggravate side reactions and irreversibility.

[0044] The uniformity and growth morphology of zinc deposition depend on the deposition and dissolution behavior of zinc. Therefore, regulating the distribution, transport and deposition kinetics of zinc ions on the interface is the key to achieving high-performance zinc anode.

[0045] In the present application, a basic zinc sulfate layer is uniformly generated in situ on the surface of the zinc negative electrode, which is equivalent to forming a uniform protective layer on the surface of the zinc negative electrode. The chemical formula of basic zinc sulfate is Zn4(OH)6SO4·xH2O, where x is the number of hydrates. The protective layer has a uniform zinc ion mass transfer channel and a high zinc ion conductivity, which can effectively regulate the uniform deposition of zinc ions and avoid the growth of zinc dendrites. At the same time, the low electronic conductivity and physical shielding effect of the basic zinc sulfate protective layer isolate the contact between the electrolyte and metallic zinc, preventing the occurrence of side reactions such as corrosion and hydrogen evolution. Therefore, the modified zinc negative electrode prepared by the present application is used as the negative electrode material of the aqueous zinc ion battery, which can improve the cycle stability and coulomb efficiency of the battery.

[0046] In addition, a uniform basic zinc sulfate protective layer can be generated at a designed portion of the surface of the zinc negative electrode substrate as required. The modified zinc negative electrode of the present application scheme only needs to generate a basic zinc sulfate layer on one side of the zinc negative electrode substrate. The basic zinc sulfate layer side of the modified zinc negative electrode is in contact with the diaphragm, which plays a role in regulating zinc ion deposition and inhibiting dendrite growth. The other side of the modified zinc negative electrode is used to contact the stainless steel casing of the battery to ensure good electronic conductivity between the zinc negative electrode and the stainless steel casing.

[0047] In some embodiments, the thickness of the basic zinc sulfate layer is 3 μm to 60 μm.

[0048] By regulating the thickness of the basic zinc sulfate layer, the effect of inhibiting the corrosion of the zinc negative electrode can be enhanced. The increase in the thickness of the basic zinc sulfate layer can more effectively hinder the electron transfer, which is beneficial to inhibit the side reactions of the zinc negative electrode. However, since basic zinc sulfate also hinders the transfer of zinc ions, an excessively thick basic zinc sulfate layer will lead to an excessively large deposition overpotential of the zinc negative electrode, which will be detrimental to the performance of the zinc negative electrode.

[0049] In some embodiments, the zinc negative electrode substrate comprises at least one of zinc foil, zinc foam, or electroplated zinc.

[0050] In some embodiments, the thickness of the zinc negative electrode substrate is 0.01 mm to 0.5 mm.

[0051] A second aspect of the embodiment of the present application provides a method for preparing a modified zinc negative electrode, comprising the following steps:

[0052] The zinc negative electrode substrate is placed in a soaking solution for soaking treatment, wherein the soaking solution includes a first solution, and the first solution is a sulfate aqueous solution. A basic zinc sulfate layer is in situ grown on the surface of the zinc negative electrode substrate to obtain a modified zinc negative electrode.

[0053] In rechargeable aqueous zinc metal batteries using zinc sulfate as the electrolyte, loose and porous basic zinc sulfate will inevitably form on the surface of the unmodified original zinc negative electrode during the charge and discharge cycle. This basic zinc sulfate structure will aggravate the side reactions of the zinc negative electrode (such as corrosion).

[0054] Therefore, by immersing the zinc negative electrode in a sulfate aqueous solution (i.e., the solution for the immersion treatment described below), the zinc negative electrode immersed in the sulfate aqueous solution will corrode and generate zinc ions due to the low redox potential of metallic zinc. The solubility of basic zinc sulfate (Ksp = 2.51×10 -56 ) is very low, therefore, when the concentrations of sulfate, hydroxide and zinc ions reach the saturation concentration of basic zinc sulfate, a dense and uniform basic zinc sulfate layer can be in situ grown on the surface of the zinc negative electrode, and the basic zinc sulfate layer is used to improve the stability and reversibility of the zinc negative electrode.

[0055] The present application obtains a modified zinc negative electrode having a basic zinc sulfate protective layer in situ grown on its surface by immersing the zinc negative electrode substrate in a sulfate aqueous solution. The preparation method is simple, the reaction conditions are mild, and it is suitable for large-scale production.

[0056] In some embodiments, the solute of the sulfate aqueous solution includes at least one of zinc sulfate, sodium sulfate, potassium sulfate or ammonium sulfate. For example, the sulfate aqueous solution is zinc sulfate; or, the sulfate aqueous solution is sodium sulfate; or, the solute of the sulfate aqueous solution is a mixture of zinc sulfate and sodium sulfate; or, the solute of the sulfate aqueous solution is a mixture of zinc sulfate, sodium sulfate and ammonium sulfate; or, the sulfate aqueous solution is a mixture of sodium sulfate and potassium sulfate, etc. The solvent of the sulfate aqueous solution is deionized water.

[0057] The reaction principle of in-situ growth of a basic zinc sulfate layer on the surface of the zinc negative electrode substrate after the zinc negative electrode substrate is immersed in a sulfate aqueous solution is:

[0058] Zn-2e - →Zn 2+ ;

[0059] 2H2O+2e - →H2↑+2OH - ;

[0060] 4Zn 2+ +6OH - +SO4 2- +xH2O→Zn4(OH)6SO4·xH2O.

[0061] It can be known from the above reaction principle that the formation of the basic zinc sulfate layer requires the participation of zinc ions. Therefore, when the solute of the sulfate aqueous solution contains zinc sulfate, the zinc ion concentration in the zinc sulfate solution is higher, and the zinc negative electrode substrate can generate the basic zinc sulfate layer more quickly. When the solute of the sulfate aqueous solution does not contain zinc sulfate, the zinc ions required for the in-situ growth of the basic zinc sulfate layer on the surface of the zinc negative electrode substrate come from the corrosion of the zinc negative electrode substrate, so it takes a longer time in the immersion treatment step to form a complete basic zinc sulfate layer on the zinc negative electrode substrate.

[0062] In some embodiments, the soaking treatment time is 12 hours to 120 hours.

[0063] In some embodiments, the temperature of the immersion treatment is 25°C to 40°C.

[0064] In some embodiments, the pH of the soaking solution is 2-7.

[0065] In some embodiments, the concentration of the sulfate aqueous solution is 0.1 mol / L to 3 mol / L.

[0066] When the concentration of the sulfate solution is 0.1 mol / L, the zinc negative electrode is immersed in the sulfate solution, and a dense and uniform basic zinc sulfate layer can be grown in situ on the surface of the zinc negative electrode. As the concentration of the sulfate solution increases, the thickness of the basic zinc sulfate layer increases. When the concentration of the sulfate solution is greater than 3 mol / L, the thickness of the generated basic zinc sulfate layer is too large, which reduces the performance of the zinc negative electrode. Therefore, the concentration of the sulfate solution is controlled at 0.1 mol / L to 3 mol / L.

[0067] In some embodiments, the soaking solution further includes a second solution, which is an aqueous solution containing at least one anion selected from the group consisting of chloride ions, fluoride ions, acetate ions, and phosphate ions.

[0068] In some embodiments, the soaking treatment includes the following steps: soaking the zinc negative electrode substrate in a first solution, and then transferring the zinc negative electrode substrate to a second solution for soaking.

[0069] Experiments have found that, on the basis of soaking the zinc negative electrode substrate in a sulfate aqueous solution, soaking the zinc negative electrode substrate in a solution containing the above-mentioned anions can effectively improve the life of the zinc negative electrode. The reason for this may be that the introduction of the above-mentioned anions into the soaking solution can regulate the structure of basic zinc sulfate and further improve the cycle stability of the zinc negative electrode. Taking chloride ions as an example, after the chloride ions are introduced into the sulfate aqueous solution, the chloride ions will form a stable chemical bond with the crystal skeleton, and then after being inserted into the basic zinc sulfate, the interlayer spacing will be further increased. The expansion of the interlayer spacing of the basic zinc sulfate layer is conducive to the transmission of zinc ions. At the same time, the negatively charged chloride ions can promote the interlayer transmission of zinc ions.

[0070] In some embodiments, in the soaking step, the solution is in a static state.

[0071] In some embodiments, the zinc negative electrode substrate is pretreated and then placed in a soaking solution, and the pretreatment includes the following steps: placing the zinc negative electrode substrate in an organic solvent for ultrasonic treatment.

[0072] In some embodiments, the ultrasonic treatment time is 4 min to 8 min.

[0073] Ultrasonic treatment in an organic solvent before immersion treatment of the zinc negative electrode substrate can remove impurities on the surface of the zinc negative electrode substrate, so as to facilitate in-situ growth of a dense and uniform basic zinc sulfate layer on the surface of the zinc negative electrode substrate.

[0074] In some embodiments, the organic solvent includes at least one of ethanol, isopropanol, or acetone.

[0075] A third aspect of an embodiment of the present application provides an aqueous zinc ion battery, comprising a negative electrode, a positive electrode and an electrolyte, wherein the negative electrode is the modified zinc negative electrode as described above, and the electrolyte is an aqueous solution.

[0076] The aqueous zinc ion battery provided in the present application adopts the modified zinc negative electrode provided in the present application, which improves the problem of corrosion and side reactions such as hydrogen evolution of the zinc negative electrode, and achieves significant improvements in coulombic efficiency and cycle stability.

[0077] In some embodiments, the positive electrode includes at least one of manganese dioxide, vanadium pentoxide, sodium vanadate, copper vanadate, zinc vanadate, activated carbon, or polyaniline.

[0078] In some embodiments, the aqueous zinc ion battery further comprises a separator for separating the positive electrode from the negative electrode, wherein the separator comprises at least one of a glass fiber separator, a nanocellulose separator, a polyolefin separator, and a hydrogel separator.

[0079] In some embodiments, the aqueous zinc ion battery is any one of a button battery, a soft pack battery or a cylindrical battery.

[0080] The following describes the invention in conjunction with specific embodiments.

[0081] Example 1

[0082] A modified zinc negative electrode comprises a zinc negative electrode substrate and a basic zinc sulfate layer coated on the surface of the zinc negative electrode substrate, wherein the basic zinc sulfate layer is obtained by an in-situ deposition reaction on the surface of the zinc negative electrode substrate.

[0083] The modified zinc anode is prepared by the following steps:

[0084] Pretreatment: A zinc negative electrode substrate (zinc foil) with a thickness of 0.1 mm and an area of ​​5 cm×6 cm was immersed in an organic solvent (ethanol) and ultrasonically treated for 5 min to remove surface impurities. The substrate was taken out and dried naturally in the air.

[0085] Prepare a solution for immersion treatment: weigh a certain mass of zinc sulfate heptahydrate (chemical formula: ZnSO4·7H2O) and dissolve it in deionized water to prepare a zinc sulfate aqueous solution with a concentration of 0.5 mol / L.

[0086] Immersion treatment: Use insulating tape to seal one side of the pretreated zinc negative electrode substrate to ensure that the basic zinc sulfate layer grows in situ only on the exposed surface (the side of the zinc negative electrode substrate that has not been sealed is defined as the exposed surface). The zinc negative electrode substrate is placed horizontally in a watch glass (10 cm in diameter) containing 80 mL of the above-mentioned zinc sulfate aqueous solution, so that the zinc negative electrode substrate is completely immersed in the zinc sulfate aqueous solution. After standing and soaking for 30 hours at 28°C, take it out, rinse it with deionized water and ethanol three times respectively, and then dry it naturally to obtain a modified zinc negative electrode.

[0087] Embodiment 2-9

[0088] The difference between Example 2-9 and Example 1 is that the solution parameters and step parameters of the immersion treatment are different, see Table 1 for details, and the rest are the same as Example 1 and will not be repeated here.

[0089] Example 10

[0090] A modified zinc negative electrode comprises a zinc negative electrode substrate and a basic zinc sulfate layer coated on the surface of the zinc negative electrode substrate, wherein the basic zinc sulfate layer is obtained by an in-situ deposition reaction on the surface of the zinc negative electrode substrate.

[0091] The modified zinc anode is prepared by the following steps:

[0092] Pretreatment: A zinc negative electrode substrate (zinc foil) with a thickness of 0.1 mm and an area of ​​5 cm×6 cm was immersed in an organic solvent (ethanol) and ultrasonically treated for 5 min to remove surface impurities. The substrate was taken out and dried naturally in the air.

[0093] Prepare the first solution for immersion treatment: weigh a certain mass of zinc sulfate heptahydrate (chemical formula: ZnSO4·7H2O) and dissolve it in deionized water to prepare a zinc sulfate aqueous solution with a concentration of 2.0 mol / L.

[0094] Prepare the second solution for immersion treatment: weigh a certain mass of zinc chloride and dissolve it in deionized water to prepare a zinc chloride aqueous solution with a concentration of 2.0 mol / L.

[0095] Soaking treatment: Use insulating tape to seal one side of the pretreated zinc negative electrode substrate to ensure that the basic zinc sulfate layer grows in situ only on the exposed surface. The zinc negative electrode substrate is placed horizontally in a watch glass (10 cm in diameter) containing 80 mL of the above-mentioned first solution (zinc sulfate aqueous solution), so that the zinc negative electrode substrate is completely immersed in the zinc sulfate aqueous solution, and is taken out after standing and soaking for 25 hours at 28°C, and is rinsed with deionized water and ethanol three times respectively, and then naturally dried. The zinc negative electrode substrate is then placed horizontally in a watch glass containing 80 mL of the above-mentioned second solution (zinc chloride aqueous solution), so that the zinc negative electrode substrate is completely immersed in the zinc chloride aqueous solution, and is taken out after standing and soaking for 25 hours at 28°C, and is rinsed with deionized water and ethanol three times respectively, and then naturally dried to obtain a modified zinc negative electrode. In this embodiment, the soaking treatment time is 50 hours in total.

[0096] Table 1 Parameter changes of Examples 1-10

[0097]

[0098] Application Example 1

[0099] The modified zinc negative electrode prepared in Example 1 was used to prepare an aqueous zinc ion battery and the battery performance was tested.

[0100] The preparation steps of aqueous zinc ion battery are as follows:

[0101] Pretreatment: The insulating tape wrapped on the surface of the modified zinc negative electrode prepared in Example 1 was removed, and the modified zinc negative electrode was cut into circular electrode sheets with a diameter of 12 mm using a cutting machine to obtain modified zinc electrode sheets.

[0102] Assemble symmetrical batteries: The modified zinc electrode sheets after pretreatment are used as both the positive and negative electrodes of the battery to assemble into symmetrical batteries. A glass fiber with a diameter of 18 mm is used as a diaphragm, and a 2 mol / L aqueous zinc sulfate solution is used as an electrolyte. The positive electrode sheet, the glass fiber diaphragm, and the negative electrode sheet are stacked in sequence and placed in a CR2025 button battery shell. 80 μL of 2 mol / L zinc sulfate electrolyte is drawn with a pipette to fully wet the glass fiber diaphragm. The button battery is assembled through a battery packaging machine to obtain an aqueous zinc ion battery.

[0103] The performance test is as follows:

[0104] Cyclic performance test: The battery prepared in this application example was used as the experimental group, and the battery prepared by referring to the above steps with the unmodified zinc negative electrode substrate was used as the control group, and the cyclic performance test was carried out at different constant current densities. The test conditions are: the charge and discharge current density is 5mA / cm 2 and 10mA / cm 2 , the corresponding charge and discharge surface capacities are 5 mAh / cm 2 and 10mAh / cm 2 .

[0105] Test results:

[0106] Experimental group: Figure 1 As shown in (a), the test battery is at 5 mA / cm 2 The current density and 5 mAh / cm 2 The surface capacity is maintained for 170 hours without short circuit; Figure 1 (b) shows that at 10 mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 165 hours without short circuit.

[0107] Comparison group: Figure 1 As shown in (a), the test battery is at 5 mA / cm 2 The current density and 5 mAh / cm 2 The short circuit occurred after only 49 hours of circulation at the surface capacity; Figure 1 (b) shows that at 10 mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0108] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0109] Application Example 2

[0110] The difference between this application example and application example 1 is that the modified zinc negative electrode prepared in Example 2 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0111] The preparation steps of the symmetrical battery are the same as those in Application Example 1 and will not be repeated here.

[0112] The steps for preparing an asymmetric battery are as follows:

[0113] Pretreatment: The insulating tape wrapped on the surface of the modified zinc negative electrode prepared in this example was removed, and the modified zinc negative electrode was cut into circular electrode sheets with a diameter of 12 mm using a cutting machine to obtain modified zinc electrode sheets.

[0114] Assembling an asymmetric battery: Using the modified zinc electrode sheet as the negative electrode, a copper foil with a diameter of 12 mm and a thickness of 50 μm as the positive electrode, and a zinc sulfate aqueous solution with a concentration of 2 mol / L as the electrolyte, an asymmetric battery was assembled.

[0115] The performance test is as follows:

[0116] Cyclic performance test: The symmetrical battery prepared in this application example was used as the experimental group, and the symmetrical battery prepared by referring to the above steps without modification of the zinc negative electrode substrate was used as the comparative group, and the cyclic performance tests were carried out at different constant current densities. The test conditions were: the charge and discharge current density was 2 mA / cm 2 and 10mA / cm 2 The corresponding charge and discharge surface capacities are 2 mAh / cm 2 and 10mAh / cm 2 .

[0117] Test results:

[0118] Experimental group: Figure 2 As shown in (a), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 The surface capacity is maintained for 280 hours without short circuit; Figure 2 (b) shows that at 10 mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 178 hours without short circuit.

[0119] Comparison group: Figure 2 As shown in (a), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 The battery short-circuited after only 53 hours of cycling at full capacity.

[0120] It can be seen that the modified zinc electrode sheet prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved. In addition, compared with application 1, this application example also has a charge and discharge current density of 10mA / cm 2 The charge and discharge surface capacities are 10 mAh / cm 2The cycle performance test was carried out under the conditions of , and the experimental group test battery of Application Example 1 remained without short circuit for 165 hours, while the experimental group test battery of this application example could remain without short circuit for 178 hours. It can be seen that changing the immersion treatment time has an impact on the modification effect of the zinc negative electrode.

[0121] Coulomb efficiency test: The asymmetric battery prepared in this application example was used as the experimental group, and the asymmetric battery prepared by referring to the above steps without modification of the zinc negative electrode substrate was used as the control group. The charge and discharge current density was 2 mA / cm 2 , the charge and discharge surface capacity is 2mAh / cm 2 The coulombic efficiency test was carried out under the conditions of

[0122] Test results:

[0123] Experimental group: Figure 3 As shown, the test cell is at 2 mA / cm 2 The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.41%, and there is no short circuit after 200 charge and discharge cycles.

[0124] Comparison group: Figure 3 As shown, the test cell is at 2 mA / cm 2 The current density is 2 mAh / cm 2 At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0125] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0126] Application Example 3

[0127] The difference between this application example and application example 1 is that the modified zinc negative electrode prepared in Example 3 is used to prepare an aqueous zinc ion battery and perform a battery performance test.

[0128] The performance test is as follows:

[0129] Cyclic performance test: The symmetrical battery prepared in this application example was used as the experimental group, and the symmetrical battery prepared by referring to the above steps without modification of the zinc negative electrode substrate was used as the control group. The charge and discharge current density was 10 mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 The cycle performance test was carried out under the conditions of

[0130] Test results:

[0131] Experimental group: Test battery at 10mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 182 hours without short circuit.

[0132] Comparison group: Test battery at 10mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0133] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0134] Application Example 4

[0135] The difference between this application example and application example 2 is that the modified zinc negative electrode prepared in Example 4 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0136] The preparation steps of the symmetric battery and the asymmetric battery are the same as those in Application Example 2 and will not be repeated here.

[0137] The performance test is as follows:

[0138] Cycle performance test: The cycle performance test of this application example is different from that of application example 3 in that the symmetrical battery assembled in application example 4 is used as the experimental group for the cycle performance test.

[0139] Test results:

[0140] Experimental group: Test battery at 10mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 190 hours without short circuit.

[0141] Comparison group: Test battery at 10mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0142] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0143] Coulomb efficiency test: The coulomb efficiency test of this application example is different from that of application example 2 in that the asymmetric battery assembled in application example 4 is used as the experimental group for the coulomb efficiency test.

[0144] Test results:

[0145] Experimental group: Test battery at 2mA / cm 2 The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.42%, and there is no short circuit after 240 charge and discharge cycles.

[0146] Comparison group: Test battery at 2mA / cm 2 The current density is 2 mAh / cm 2 At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0147] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0148] Application Example 5

[0149] The difference between this application example and application example 2 is that the modified zinc negative electrode prepared in Example 5 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0150] The preparation steps of the symmetric battery and the asymmetric battery are the same as those in Application Example 2 and will not be repeated here.

[0151] The performance test is as follows:

[0152] Cycle performance test: The cycle performance test of this application example is different from that of application example 3 in that the symmetrical battery assembled in application example 5 is used as the experimental group for the cycle performance test.

[0153] Test results:

[0154] Experimental group: Test battery at 10mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 135 hours without short circuit.

[0155] Comparison group: Test battery at 10mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0156] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0157] Coulomb efficiency test: The coulomb efficiency test of this application example is different from that of application example 2 in that the asymmetric battery assembled in application example 5 is used as the experimental group for the coulomb efficiency test.

[0158] Test results:

[0159] Experimental group: Test battery at 2mA / cm 2 The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.44%, and there is no short circuit after 200 charge and discharge cycles.

[0160] Comparison group: Test battery at 2mA / cm 2 The current density is 2 mAh / cm 2 At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0161] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0162] Application Example 6

[0163] The difference between this application example and application example 2 is that the modified zinc negative electrode prepared in Example 6 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0164] The preparation steps of the symmetric battery and the asymmetric battery are the same as those in Application Example 2 and will not be repeated here.

[0165] The performance test is as follows:

[0166] Cycle performance test: The cycle performance test of this application example is different from that of application example 3 in that the symmetrical battery assembled in application example 6 is used as the experimental group for the cycle performance test.

[0167] Test results:

[0168] Experimental group: Figure 4 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 220 hours without short circuit.

[0169] Comparison group: Figure 4 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0170] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0171] Coulomb efficiency test: The coulomb efficiency test of this application example is different from that of application example 2 in that the asymmetric battery assembled in application example 6 is used as the experimental group for the coulomb efficiency test.

[0172] Test results:

[0173] Experimental group: Figure 4 As shown in (b), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.34%, and there is no short circuit after 300 charge and discharge cycles.

[0174] Comparison group: Figure 4 As shown in (b), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0175] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0176] Application Example 7

[0177] The difference between this application example and application example 2 is that the modified zinc negative electrode prepared in Example 7 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0178] The preparation steps of the symmetric battery and the asymmetric battery are the same as those in Application Example 2 and will not be repeated here.

[0179] The performance test is as follows:

[0180] Cycle performance test: The cycle performance test of this application example is different from that of application example 3 in that the symmetrical battery assembled in application example 7 is used as the experimental group for the cycle performance test.

[0181] Test results:

[0182] Experimental group: Test battery at 10mA / cm2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 160 hours without short circuit.

[0183] Comparison group: Test battery at 10mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0184] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0185] Coulomb efficiency test: The coulomb efficiency test of this application example is different from that of application example 2 in that the asymmetric battery assembled in application example 7 is used as the experimental group for the coulomb efficiency test.

[0186] Test results:

[0187] Experimental group: Test battery at 2mA / cm 2 The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.24%, and there is no short circuit after 260 charge and discharge cycles.

[0188] Comparison group: Test battery at 2mA / cm 2 The current density is 2 mAh / cm 2 At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0189] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0190] Application Example 8

[0191] The difference between this application example and application example 2 is that the modified zinc negative electrode prepared in Example 8 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0192] The preparation steps of the symmetric battery and the asymmetric battery are the same as those in Application Example 2 and will not be repeated here.

[0193] The performance test is as follows:

[0194] Cycle performance test: The cycle performance test of this application example is different from that of application example 3 in that the symmetrical battery assembled in application example 8 is used as the experimental group for the cycle performance test.

[0195] Test results:

[0196] Experimental group: Figure 5 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 150 hours without short circuit.

[0197] Comparison group: Figure 5 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0198] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0199] Coulomb efficiency test: The coulomb efficiency test of this application example is different from that of application example 2 in that the asymmetric battery assembled in application example 8 is used as the experimental group for the coulomb efficiency test.

[0200] Test results:

[0201] Experimental group: Figure 5 As shown in (b), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.30%, and there is no short circuit after 210 charge and discharge cycles.

[0202] Comparison group: Figure 5 As shown in (b), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0203] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0204] Application Example 9

[0205] The difference between this application example and application example 2 is that the modified zinc negative electrode prepared in Example 9 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0206] The preparation steps of the symmetric battery and the asymmetric battery are the same as those in Application Example 2 and will not be repeated here.

[0207] The performance test is as follows:

[0208] Cycle performance test: The cycle performance test of this application example is different from that of application example 3 in that the symmetrical battery assembled in application example 9 is used as the experimental group for the cycle performance test.

[0209] Test results:

[0210] Experimental group: Figure 6 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 195 hours without short circuit.

[0211] Comparison group: Figure 6 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0212] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0213] Coulomb efficiency test: The coulomb efficiency test of this application example is different from that of application example 2 in that the asymmetric battery assembled in application example 9 is used as the experimental group for the coulomb efficiency test.

[0214] Test results:

[0215] Experimental group: Figure 6 As shown in (b), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.41%, and there is no short circuit after 300 charge and discharge cycles.

[0216] Comparison group: Figure 6 As shown in (b), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0217] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0218] Application Example 10

[0219] The difference between this application example and application example 2 is that the modified zinc negative electrode prepared in Example 10 is used in the preparation of aqueous zinc ion batteries, which are assembled into symmetrical batteries and asymmetrical batteries for cycle performance tests and coulomb efficiency tests.

[0220] The preparation steps of the symmetric battery and the asymmetric battery are the same as those in Application Example 2 and will not be repeated here.

[0221] The performance test is as follows:

[0222] Cyclic performance test: The cyclic performance test of this application example is different from that of application example 3 in that the symmetrical battery assembled in application example 10 is used as the experimental group for the cyclic performance test.

[0223] Test results:

[0224] Experimental group: Figure 7 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm 2 The surface capacity was maintained for 250 hours without short circuit.

[0225] Comparison group: Figure 7 As shown in (a), the test battery is at 10 mA / cm 2 The current density and 10 mAh / cm 2 The short circuit occurred after only 45 hours of cycling at the surface capacity.

[0226] It can be seen that the modified zinc electrode prepared by the aqueous zinc ion battery using the scheme of the present application can improve the charge and discharge cycle performance of the battery, and the battery life is significantly improved.

[0227] Coulomb efficiency test: The coulomb efficiency test of this application example is different from that of application example 2 in that the asymmetric battery assembled in application example 10 is used as the experimental group for the coulomb efficiency test.

[0228] Test results:

[0229] Experimental group: Figure 7 As shown in (b), the test battery is at 2 mA / cm 2The current density is 2 mAh / cm 2 The average coulombic efficiency at the surface capacity is as high as 99.45%, and there is no short circuit after 350 charge and discharge cycles.

[0230] Comparison group: Figure 7 As shown in (b), the test battery is at 2 mA / cm 2 The current density is 2 mAh / cm 2 At the surface capacity of 1.547 W, short circuit failure occurred after only 24 charge and discharge cycles, and the cycle stability was poor. The average coulombic efficiency of the original zinc negative electrode before short circuit was 99.16%.

[0231] It can be seen that the modified zinc electrode prepared by the scheme of the present application as the negative electrode of the battery can improve the coulombic efficiency of the battery and significantly improve the charge and discharge cycle performance.

[0232] By comparing the test results of the experimental groups in Application Examples 1, 2, and 5, it can be seen that at the same 10mA / cm 2 The current density and 10 mAh / cm 2 Under the surface capacity test conditions, as the immersion treatment time increases, the prepared zinc negative electrode is better for improving the battery's cycle performance.

[0233] By comparing the test results of the experimental groups in Application Examples 2, 6, and 7, it can be seen that at the same 10mA / cm 2 The current density and 10 mAh / cm 2 Under the surface capacity test conditions, the cycle performance of the battery improved with the increase of the concentration of zinc sulfate solution, which shows that by increasing the concentration of zinc sulfate solution within a specific concentration range, a modified zinc negative electrode with better performance can be obtained.

[0234] By comparing the test results of the experimental groups in Application Examples 3, 8, and 9, it can be seen that, under the same other conditions, the zinc negative electrode prepared by using the sulfate solution containing zinc sulfate solute is applied to the battery, and the battery charge and discharge cycle performance is better than that of the sulfate solution not containing zinc sulfate solute.

[0235] By comparing the test results of the experimental groups in Application Example 4 and Application Example 10, it can be seen that, under the same other conditions, soaking the zinc negative electrode in a sulfate solution and then continuing to soak it in a solution containing other anions can improve the cycle stability of the zinc negative electrode, thereby improving the cycle life of the battery.

[0236] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A modified zinc negative electrode, characterized in that: The invention comprises a zinc negative electrode substrate and a basic zinc sulfate layer coated on at least a part of the surface of the zinc negative electrode substrate, wherein the basic zinc sulfate layer is generated in situ on the surface of the zinc negative electrode substrate.

2. The modified zinc negative electrode according to claim 1, characterized in that The thickness of the basic zinc sulfate layer is 3 μm to 60 μm.

3. The modified zinc negative electrode according to claim 1 or 2, characterized in that: The zinc negative electrode substrate comprises at least one of zinc foil, zinc foam or electroplated zinc; and / or, The thickness of the zinc negative electrode substrate is 0.01 mm to 0.5 mm.

4. A method for preparing a modified zinc negative electrode according to any one of claims 1 to 3, characterized in that: The following steps are involved: The zinc negative electrode substrate is placed in a soaking solution for soaking treatment, wherein the soaking solution includes a first solution, and the first solution is a sulfate aqueous solution. The basic zinc sulfate layer is in situ grown on the surface of the zinc negative electrode substrate to obtain a modified zinc negative electrode.

5. The method for preparing a modified zinc negative electrode according to claim 4, characterized in that: The solute of the sulfate aqueous solution includes at least one of zinc sulfate, sodium sulfate, potassium sulfate or ammonium sulfate.

6. The method for preparing a modified zinc negative electrode according to claim 4, characterized in that: The soaking treatment time is 12h to 120h; and / or, The immersion treatment temperature is 25°C to 40°C; and / or, The pH value of the soaking solution is 2 to 7; and / or, The concentration of the sulfate aqueous solution is 0.1 mol / L to 3 mol / L.

7. The method for preparing a modified zinc negative electrode according to claim 5, characterized in that: The soaking solution also includes a second solution, which is an aqueous solution containing at least one anion selected from the group consisting of chloride ions, fluoride ions, acetate ions, and phosphate ions.

8. The method for preparing a modified zinc negative electrode according to claim 7, characterized in that: The soaking process comprises the following steps: The zinc negative electrode substrate is first placed in the first solution for soaking, and then the zinc negative electrode substrate is transferred to the second solution for soaking.

9. The method for preparing a modified zinc negative electrode according to any one of claims 4 to 8, characterized in that: The zinc negative electrode substrate is pretreated and then placed in the soaking solution, wherein the pretreatment comprises the following steps: placing the zinc negative electrode substrate in an organic solvent for ultrasonic treatment.

10. An aqueous zinc ion battery, characterized in that: The invention comprises a negative electrode, a positive electrode and an electrolyte, wherein the negative electrode is a modified zinc negative electrode as described in any one of claims 1 to 3 and / or a modified zinc negative electrode prepared by the preparation method of the modified zinc negative electrode as described in any one of claims 4 to 9.